2013
DOI: 10.3855/jidc.3540
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of Cryptosporidium spp. from animal sources in China

Abstract: This item has no abstract. Follow the links below to access the full text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 17 publications
(18 reference statements)
1
10
0
Order By: Relevance
“…Among them, C. parvum is the most common zoonotic Cryptosporidium species and has been found in humans worldwide [10, 29]. It is a zoonotic pathogen and has been reported in humans as well as in many animals in China, such as cattle, dogs, horses, birds, giant pandas, red pandas, deer, snakes, and rodents [15, 27, 30]. Cryptosporidium rat genotype II has been found in brown rats in the Philippines [20], Nigeria [1], Australia [21], and China.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, C. parvum is the most common zoonotic Cryptosporidium species and has been found in humans worldwide [10, 29]. It is a zoonotic pathogen and has been reported in humans as well as in many animals in China, such as cattle, dogs, horses, birds, giant pandas, red pandas, deer, snakes, and rodents [15, 27, 30]. Cryptosporidium rat genotype II has been found in brown rats in the Philippines [20], Nigeria [1], Australia [21], and China.…”
Section: Discussionmentioning
confidence: 99%
“…Cryptosporidiosis is suspected to be endemic in dogs across China even though only few extensive studies had been conducted. From 84 fecal samples taken from cats, dogs and from waste water of zoo drainage channels, in a study in Shanghai, China, an infection rate of 7% was reported [112]. From 545 fecal samples taken from yaks in nine different counties of central western region of China, the prevalence of Cryptosporidium spp.…”
Section: Chinamentioning
confidence: 99%
“…The remaining four nucleotide sequences (KF993721, KF993722, KF993725, and KF993727) were novel. Although two (KF993721 and KF993722) differed at two base positions, both were identical (at the amino acid level) with previous human isolates in China [24].…”
Section: Genetic Characterization Of Assemblages C D E and Fmentioning
confidence: 56%
“…Meanwhile, more attention should be paid to the health of protected animal species and endangered/threatened animal species in China. We have previously molecularly identified Cryptosporidium in pets and zoo animals [24]; it is also necessary to detect other intestinal pathogens in these animals. The present study mainly focused on the molecular epidemiological investigation of G. duodenalis in pet and zoo animals from Shanghai, China.…”
Section: Introductionmentioning
confidence: 99%